(untitled) (International journal of medical sciences, 2025)
This article analyzes the relationship between diabetes mellitus (DM) and ischemic heart disease (IHD) from clinical, epidemiological, and pathophysiological perspectives. The study results show that patients with diabetes have a 2–4 times higher risk of developing cardiovascular complications, particularly ischemic heart disease. Dyslipidemia, hyperglycemia, insulin resistance, endothelial dysfunction, and oxidative stress are the main pathogenetic mechanisms of this process.